Theoretical Aspects of Projects Estimation Using the Use Case Points Method - Wolski, Michał; Pilski, Marek (Studia Informatica. System and information technology, 2019)
This text is the first one of the series of articles concerning projects. estimation in Enterprise Architect. In this section, theoretical aspects of function points methods have been presented. Part two entitled: .Example of the Application of the Use of the Case Points Method. constitutes an example along with mathematical calculations and part three entitled: .Project Estimation with the Use of the Method of Use Cases in Enterprise Architect. is a practical application of the function points method in Enterprise Architect.